A retrospective review of low-birth-weight cases in a tertiary care hospital in Shimla district of Himachal Pradesh - Sharma, Rakesh; Kumar, Pancham; Sood, Ambika; Roach, Vipin (International Journal of Contemporary Pediatrics, 2021)
Background: Low birth weight (LBW) is a serious public health problem and a leading cause of death in the first month of life. The present study aimed to study the trends of low birth weight in Shimla district of Himachal Pradesh, India. Methods: Retrospective review of records of Kamla Nehru Hospital, Shimla covering the period January 2016 to December 2020 was done. The total number of low-birth-weight babies each year were retrieved. Results: A total of 34769 live births took place in Kamla Nehru Hospital, Shimla from 2016 to 2020. Among the total live births, 8479 (24.39%) were having low birth weight (<2500 gm) while 26290 (75.61%) were having normal birth weight (>2500 gm). Out of total 8479 LBW Babies, 7148 (84.3%) were LBW (<2500 gm),1167 (13.76%) were very low birth weight (1000-1500 gm) and 164 (1.93%) were of extremely low birth weight There was continuous decrease in low birth weight from 35.14% in 2016 to 17.51% in 2019. After that it start increasing slightly to 18.9% in 2020. Conclusions: Over the span of five years, there was continuous decrease in incidence of LBW. Nutritional education during pregnancy and proper Antenatal care (ANC) services needs to be addressed to reduce prevalence of LBW in Himachal Pradesh